Dietary Patterns are Significantly Associated with Hypertension Among Older Adults - Eka SR Sihombing; Nur Masdalifah Masdalifah; Amanda Faradihita; Christian Rayando Butar-butar; Wandha Wandha (FORIKES, 2026)
Hypertension remains a major public health concern among older adults, particularly in low‑ and middle‑income settings where lifestyle factors such as dietary patterns contribute substantially to disease burden. This study aimed to determine the relationship between dietary patterns and the occurrence of hypertension among older adults in the working area of BP Nauli Health Center, Pematangsiantar, in 2024. This study employed a quantitative analytic observational design using an ex post facto approach. The research was conducted from May to August 2024. A total of 2,813 older adults constituted the study population, from which 107 respondents were selected using purposive sampling. Dietary patterns were assessed based on frequency, type, and quantity of food consumed, while hypertension status was classified according to WHO criteria. Data were analyzed using descriptive statistics and Spearman’s rho correlation test. More than half of the respondents (52.3%) exhibited poor dietary patterns. Hypertension Grade 2 was more prevalent (63.6%) than Grade 1 (36.4%). Cross‑tabulation showed that respondents with poor dietary patterns had a higher proportion of Grade 2 hypertension (60.3%). Bivariate analysis using Spearman’s rho revealed a significant relationship between dietary patterns and hypertension (p = 0.03; α = 0.05), indicating that poorer dietary patterns were associated with higher hypertension severity. In conclusion, dietary patterns are significantly associated with hypertension among older adults. These findings highlight the importance of improving nutritional behavior as part of community‑based hypertension prevention and control strategies.Keywords: dietary pattern; hypertension; older adults